Antioxidant Activity, Sun Protection Factor and Phytochemical Properties of Different Parts Sawo Walanda (Pouteria Campechiana (Kunth.) B.) Extract - Fitriansyah, Sani Nurlaela; Fadhilah, Syifa; Ruslan, Komar; Hartati, Rika; Fidrianny, Irda (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
AbstractUV radiation can lead production of Reactive Oxygen Species (ROS) on the skin and can cause negative effects1. Sun protector and antioxidant ingredients are needed to protect the skin2. Phenolic compounds and flavonoids have been used as sun protectors and as antioxidants3. Pouteria campechiana is known for its high abundance of phenolic compounds4. This study reported the phytochemical group, total phenol and total flavonoid content, antioxidant activity, and sun protector factor of ethanol extracts of pulp, seed, leaves, and twigs of Pouteria campechiana. Determination of antioxidant activity, sun protection factor, and total phenol and total flavonoid content were carried out using UV-visible spectrophotometry. Crude drugs and extract of pulp, seed, twig, and leaves P.campechiana containing phenolic group, tannin, and flavonoid. The leaf extract had the highest total phenolic content, while the highest total flavonoid content was in the seed extract. All of the extracts tested had very strong antioxidant activity indicated by the Antioxidant Activity Index (AAI) to DPPH value, >2. At a concentration of 1000 µg/mL, the leaf extract showed the highest SPF value, 16.01 ± 0.38.The conclusion, the leaf extract had the potential to further as a natural antioxidant, and sun protector. AbstrakPaparan radiasi UV dapat meningkatkan produksi Reactive Oxygen Species (ROS) sebagai radikal bebas dan dapat menimbulkan efek negatif pada kulit. Dibutuhkan senayawa aktif sebagai fotoprotektor dan senyawa penangkal radikal bebas yang disebut antioksidan untuk melindungi kulit. Golongan senyawa fenol dan flavonoid dapat menyerap radiasi UV dan menangkal radikal bebas. Pouteria campechiana dilaporkan mengandung senyawa fenol. Penelitian ini melaporkan golongan senyawa kimia, kadar fenol dan flavonoid total, aktivitas antioksidan terhadap DPPH dan aktivitas fotoprotektor yang menggunakan parameter nilai Sun Protector Factor (SPF) dari ekstrak etanol daging buah, biji, ranting dan daun Poteria campechiana. Ativitas antioksidan, nilai SPF, kadar fenol total, dan flavonoid total diukur secara spektrofotometri UV-Sinar tampak. Hasil penelitin menunjukkan simplisia dan ekstrak etanol daging buah, biji, ranting dan daun P.campechiana mengandung golongan senyawa fenoli, tanin, dan flavonoid. Ekstrak etanol daun memiliki kadar fenol total tertinggi, sedangkan kadar flavonoid total tertinggi ada pada ekstrak etanol biji. Keempat ekstrak tergolong pada antioksidan sangat kuat, dengan parameter nilai AAI >2. Pada konsentrasi 1000 µg/mL, ekstrak daun menunjukkan nilai SPF tertinggi yaitu sebesar 16,01 ± 0,38. Kesimpulan, ekstrak etanol daun P.campechiana lebih berpotensi untuk dikembangkan sebagai bahan baku aktif antioksidan alami dan fotoprotektor.